2011
DOI: 10.1007/s11010-011-1088-7
|View full text |Cite
|
Sign up to set email alerts
|

9-Phenyl acridine exhibits antitumour activity by inducing apoptosis in A375 cells

Abstract: Several acridine derivatives have been screened for their therapeutic potential and some are already established as antiprotozoan, antibacterial or anticancer agents. However, phenyl derivative at C-9 position of acridine had remained unexplored for their biological activity so far. In this report, we present our findings with 9-phenyl acridine (ACPH) as an anticancer agent. Both A375 and HeLa, two human cancer cell lines, were more sensitive to ACPH than normal cells namely human lymphocytes and also Chinese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Recent research has revealed two human cancer cell lines, A375 and Hela, which are more sensitive to ACPH than normal cells, namely human lymphocytes and Chinese hamster V79 cells. [41] In the present study, we verified the capability of graphiteassisted laser desorption single photon ionization mass spectrometry for the direct and fast analysis of the low molecular weight drug ACPH within complex biological tissues such as mice kidney. The potential of this technique for the quantification of small molecule drugs was also demonstrated by determining the detection sensitivity and acquiring a drug-time curve of ACPH in mice kidney.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Recent research has revealed two human cancer cell lines, A375 and Hela, which are more sensitive to ACPH than normal cells, namely human lymphocytes and Chinese hamster V79 cells. [41] In the present study, we verified the capability of graphiteassisted laser desorption single photon ionization mass spectrometry for the direct and fast analysis of the low molecular weight drug ACPH within complex biological tissues such as mice kidney. The potential of this technique for the quantification of small molecule drugs was also demonstrated by determining the detection sensitivity and acquiring a drug-time curve of ACPH in mice kidney.…”
supporting
confidence: 63%
“…In the present research, we used 9‐phenylacridine (ACPH) as the model drug molecule, as this compound, a DNA minor groove binder, has proven antitumour activity. Recent research has revealed two human cancer cell lines, A375 and Hela, which are more sensitive to ACPH than normal cells, namely human lymphocytes and Chinese hamster V79 cells …”
mentioning
confidence: 99%
“…There are several possibilities to explain this phenomena: 1) in vitro, a 1 M dose is not high enough to trigger apoptosis, although it is potent enough to elicit cell cycle arrest and inhibits EGFR and PKCs; 2) in vivo, at doses of 50 or 100 mg/kg, the real drug exposure for C2 is more than 1 M in tumor samples, hence, the apoptosisinducing effect is evident in the tumors; 3) it is possible that C2 can be metabolized after oral administration, and changed into modified derivatives. For instance, some 9-position modified acridine elicited apoptosis in numerous human cancers (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly important are the derivatives at C 9 position [16,17].The biological activities of phenyl-derivatives at C 9 position were so far less explored. From our earlier works the biological importance of some aryl derivatives of acridine are already documented [18,19] and the antitumor action have been demonstrated in different cancer cell lines as well as in animal model [20]. Aryl acridine derivatives can also potentiate cell killing by other agents (our unpublished results).…”
Section: Introductionmentioning
confidence: 68%